Pancasila Legal Philosophy: Ethical and Ontological Foundations Indonesian Legal System - Suci Naylul Muna; Nurlaila; Zulfan, Zulfan (International Journal of Law, Social Science, and Humanities, 2026)
This research examines in depth the aspects of legal philosophy related to Pancasila as the ontological and ethical basis in the structure of Indonesian law. From an ontological perspective, Pancasila is determined as the existential essence (causa prima) of national law, which originates from the cultural-religious values of Indonesian society and is manifested in hierarchical-pyramidal principles. In an ethical context, Pancasila serves as a legal ideal (rechtsidee) and basic moral norm that guides the creation, interpretation, and implementation of laws to achieve Social Justice. This type of research is normative-philosophical using conceptual, historical, and legislative methods. The results of the study indicate that the neglect of the ontological and ethical dimensions of Pancasila has led to a crisis of legal legitimacy and disorientation in progressive law enforcement. Thus, a reactualization and recontextualization of the Pancasila Legal Philosophy is needed as a Staats fundamental norm that is the soul of the entire legal system, from the grund norm to the implementing regulations, to ensure moral integrity and substantive justice in the Indonesian legal system.